ISOLASI DNA TANAMAN PADI (Oryza sativa L.) ASAL KECAMATAN BANTAN, BENGKALIS – RIAU. - Dita Deanesia; Dewi Indriyani Roslim; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Excess  of  Fe  in  costal  land  in  Riau Province  is potential to  poison the  roots  of  plants. However,the plants have their  own  mechanism  to overcome  the Fe overload.  This  study was aimed  to  isolate  the total   DNAof rice plants among  three  local  rice genotypes  from Riau  which are  commonly  planted in costal  land  in  Bengkalis,  Riau, with  Fe overload resistant  swamp  rice variety  (Mahsuri)  and Fe overload sensitive rice variety  (IR64). The experiment was conducted  in the Laboratory of Genetics, FMIPA UR,from January to May   2014. Research methods  consisted of  isolation  of DNA  and  electrophoresis.  In this study  isolation of DNA  from five rice  varieties  was succesfully done. Among those DNA, concentration  of  total DNA  which were  obtained from IR64 and Amat Candu were very high.